A Remarkably Long Remission Achieved with Ibrutinib Monotherapy in a Patient who was Diagnosed with Steroid Refractory Sclerosing Chronic GVHD - Sevindik, Omur Gokmen; Merter, Mustafa (Springernature, 2020)
[Abstract Not Available]